2016
DOI: 10.1016/j.conbuildmat.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of slag content and water-binder ratio on leaching behavior of cement pastes

Abstract: In order to obtain quickly the influences of blast furnace slag and water-binder ratio on the leaching behavior of cement-based material and its corrosion resistance in water environments, an accelerated calcium leaching experiment on a slice specimen with slag-cement pastes in 6M NH 4 Cl solution was carried out. Using the saturation-drying weighing method, X-ray diffraction (XRD) and the scanning electron microscope (SEM/EDS) measurement, the influences of water-binder ratio and slag content on the porosity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
4

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 37 publications
2
16
0
4
Order By: Relevance
“…The initial porosity of cement paste has a large impact on its calcium leaching process. Tang has [59] reported that the reduction of water-binder ratio improved the compactness and initial porosity of slag cement pastes, and decreased the diffusion rate of calcium ions in pore solution, leading to an enhanced calcium leaching resistance. On the contrary, large initial porosity leads to a decreased leaching resistance.…”
Section: Self-degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial porosity of cement paste has a large impact on its calcium leaching process. Tang has [59] reported that the reduction of water-binder ratio improved the compactness and initial porosity of slag cement pastes, and decreased the diffusion rate of calcium ions in pore solution, leading to an enhanced calcium leaching resistance. On the contrary, large initial porosity leads to a decreased leaching resistance.…”
Section: Self-degradationmentioning
confidence: 99%
“…Besides that, contact with pure water creates concentration gradients between the interstitial solution and the aggressive environment of these cementitious materials, as a result of which some ions in the pore solution diffuse outwards into the aggressive solution. The leaching process has been investigated previously [57][58][59].…”
Section: Self-degradationmentioning
confidence: 99%
“…The reduction in concentration of calcium ions in the pore solution forces the dissolution of calcium hydroxide and calcium-silicate-hydrate gel and decrease the alkalinity of the pore solution [12,13]. Calcium leaching also causes the increased porosity, and permeability of material and the reduction of concrete strength [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…These aggressive agents can easily deteriorate the structures, causing the reduction in material durability and performance [2,3]. This is thus a challenging problem mainly because of significant maintenance costs [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation